دور حاضنات الاعمال في تطوير المؤسسات الناشئة -دراسة حالة لحاضنة أعمال جامعة الوادي والمؤسسة الناشئة HB tronics بالوادي - رقية مفتاح; مروى غنامي; وداد ذهب; إبراهيم ذهب (university of eloued جامعة الوادي, 2024)
"تهدف هذه الدراسة معرفة الدور الذي تلعبه حاضنات الأعمال في تطوير النظام البيئي للمؤسسات الناشئة، حيث تم إجراء الدراسة التطبيقية على مستوى كل من حاضنة أعمال بالوادي والمؤسسة الناشئة HB"" "" باTRONICSلوادي , ومن أجل بلوغ الأهداف تم الاعتماد في هذه الدراسة على المنهج الوصفي التحلي الذي يقوم على تقديم الأدبيات الاقتصادية حول حاضنات الأعمال والمؤسسات الناشئة والعلاقة التي تربطهم , لتبيي دور حاضنة اعمال الوادي في تحسي وتطوير النظام البيئي للمؤسسة الناشئة ""HB TRONICS"" بالوادي. توصلت الدراسة إلى ان حاضنة الأعمال بالوادي, لها دور جوهريكبير في مساهمة انشاء مؤسسة ""HB TRONICS"" من خلال مرافقتها واحتضانها في مراحل نموها , من مرحلة تقديم المشروع الى مرحلة تخرجه من الحاضنة ,كما عملت على إبرازها في السوق وتدريبها وتحويل هذه الفكرة الى واقع مجسد , بالإضافة الى دعمها وفتح افاق لها في عدة جوانب تقنية وفنية وقانونية " "This study aims to understand the role played by business incubators in developing the ecosystem for startups. The empirical study was conducted at both the business incubator in El Oued and the startup ""HB TRONICS"" in El Oued. In order to achieve the goals, the study relied on a descriptive methodology, which presents economic literature on business incubators, startups, and their relationship, using data collection tools such as interviews and their analysis to illustrate the role of business incubators in improving the ecosystem at ""HB TRONICS."" The study found that the business incubator in El Oued plays a significant and essential role in contributing to the establishment of ""HB TRONICS"" by accompanying and nurturing it through its growth stages, from project submission to graduation from the incubator. Additionally, it worked on highlighting it in the market, training it, and turning this idea into a tangible reality. Moreover, it provided support and opened up avenues for it in various technical, artistic, and legal aspects."
Keywords: حاضنات الاعمال، مؤسسات الناشئة، حاضنة اعمال جامعة الوادي، مؤسسة "HB TRONICS" بالوادي، نظام البيئ; business incubators; startups; El Oued Business Incubator; HB TRONICS; ecosystem